Atomically-resolved edge states on surface-nanotemplated graphene explored at room temperature. Issue 11 (6th March 2017) - Merino, Pablo; Santos, Hernán; Pinardi, Anna L.; Chico, Leonor; Martin-Gago, José A.
Abstract : Graphene edges present localized electronic states strongly depending on their shape, size and border configuration. Abstract : Graphene edges present localized electronic states strongly depending on their shape, size and border configuration. Chiral- or zigzag-ended graphene nanostructures develop spatially and spectrally localized edge states around the Fermi level; however, atomic scale investigations of such graphene terminations and their related electronic states are very challenging and many of their properties remain unexplored. Here we present a combined experimental and theoretical study on graphene stripes showing strong metallic edge states at room temperature. By means of scanning tunneling microscopy, we demonstrate the use of vicinal Pt(111) as a template for the growth of graphene stripes and characterize their electronic structure. We find the formation of a sublattice localized electronic state confined on the free-standing edges of the graphene ribbons at energies close to the Fermi level. These experimental results are reproduced and understood with tight-binding and ab initio calculations. Our results provide a new way of synthesizing wide graphene stripes with zigzag edge termination and open new prospects in the study of valley and spin phenomena at their interfaces.